2006
DOI: 10.1007/s00436-005-0107-6
|View full text |Cite
|
Sign up to set email alerts
|

Ribosomal DNA second internal transcribed spacer sequence studies of Culicid vectors from an endemic area of Dirofilaria immitis in Spain

Abstract: Studies were performed in an endemic area of Dirofilaria immitis in Spain to genetically characterize the potential mosquito vector species present by means of DNA sequencing and elucidate which of these species may be involved in the transmission. The rDNA ITS-2 sequences of two Culex pipiens haplotypes, H1 and H2, Aedes (Aedimorphus) vexans, Fredwardsius vittatus, Ochlerotatus (Ochlerotatus) caspius, Anopheles (Anopheles) atroparvus, and Anopheles (Anopheles) plumbeus were obtained. F. vittatus and An. plumb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 38 publications
1
12
0
Order By: Relevance
“…pipiens higher abundances and parasite development in the vector ( Roiz et al, 2014 andSassnau et al, 2014). Regardless of the observed monophasic distribution, mosquitoes were nevertheless captured throughout the year, as previously ( Bargues et al, 2006 andRoiz et al, 2015). This probably reflects an outstanding environmental adaptation capacity of Cx.…”
Section: Discussionmentioning
confidence: 85%
See 3 more Smart Citations
“…pipiens higher abundances and parasite development in the vector ( Roiz et al, 2014 andSassnau et al, 2014). Regardless of the observed monophasic distribution, mosquitoes were nevertheless captured throughout the year, as previously ( Bargues et al, 2006 andRoiz et al, 2015). This probably reflects an outstanding environmental adaptation capacity of Cx.…”
Section: Discussionmentioning
confidence: 85%
“…According to Bargues et al (2006) and Morchón et al (2007), the analysis of nuclear rDNA ITS-2 sequences allows validation of the classification and haplotype characterization of mosquitoes. These studies suggested that haplotype H1 may be genetically ascribed to Cx.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The molecular markers used for the characterisation of Cx. theileri were selected according to previous results having shown their usefulness for mosquitoes in general or Culicids in particular: small subunit or 18S rRNA gene [18][19][20][21] and the second internal transcribed spacer ITS-2 [22][23][24][25] within the nuclear rDNA, and the cytochrome c oxidase subunit I cox1 [9, within the mtDNA. This finding represents a new record for vector species not only for the Canary Island fauna but also for the whole Spanish country where the only mosquito species involved in D.…”
Section: Introductionmentioning
confidence: 99%